1995
DOI: 10.1002/cne.903580412
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid cycling proteins redistribute in light‐/dark‐adapted octopus retinas

Abstract: In cephalopods, the complex rhodopsin-retinochrome system serves to regenerate metarhodopsin and metaretinochrome after illumination. In the dark, a soluble protein, retinal-binding protein (RALBP), shuttles 11-cis retinal released from metaretinochrome located in the photoreceptor inner segments to metarhodopsin present in the rhabdoms. While in the rhabdoms, RALBP delivers 11-cis retinal to regenerate rhodopsin and in turn binds the all-trans isomer released by metarhodopsin. RALBP then returns all-trans ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…This may be an oversimplification of a more complicated process involving interesting light-dependent changes in the distribution of the key proteins. In a detailed scanning confocal microscopy study, Robles et al (1995) showed that in addition to rhodopsin, retinochrome is present in the rhabdomal compartment. In the dark, opsin and retinochrome co-localize at the base of the rhabdomal microvilli.…”
Section: Moving Retinoids Between Cellular Sites Of Cismentioning
confidence: 99%
“…This may be an oversimplification of a more complicated process involving interesting light-dependent changes in the distribution of the key proteins. In a detailed scanning confocal microscopy study, Robles et al (1995) showed that in addition to rhodopsin, retinochrome is present in the rhabdomal compartment. In the dark, opsin and retinochrome co-localize at the base of the rhabdomal microvilli.…”
Section: Moving Retinoids Between Cellular Sites Of Cismentioning
confidence: 99%
“…An extracellular function would be consistent with the recent evidence suggesting that RFABG is related to insect lipophorins, secreted fatty acid carriers (Kutty et al, 1996). It is noteworthy that retinochrome in the octopus is also seen extracellularly in light adapted eyes (Robles et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Based on previous research in the blowfly (Schwemer, 1993) and honeybee (Smith and Goldsmith, 1991) which showed that vitamin A and photoisomerase are localized distally, the Semper cells, also distal, are prime candidates for involvement in retinoid metabolism. It was suggested that retinochrome and retinal binding protein may be expressed in supportive cells in the octopus (Robles et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising, as molluscan systems have shown potential for study of basic visual processes, physiology of vision, development of the visual system, and evolution. For example, past work (Robles et al 1995, Torres et al 1997 has shown that cytoskeletal organization of photoreceptor cells is regulated by the state of light-and dark-adaptation in cephalopod eyes. It is known that some disease states in the human retina, such as macular degeneration, affect cytoskeletal development and organization (Eckmiller 2004).…”
Section: Molluscs As "Non-traditional" Model Organisms For Studying Tmentioning
confidence: 99%
“…Other work on the cephalopod retina has focused on light/dark adaptation-how the eye acclimates to changes in light levels in the environment (Young 1963a). Work on cephalopods has identified important sub-cellular alternations to the shape of photoreceptor cells and movements of cytoskeleton and photopigments within these cells in response to changes in light intensity (Robles et al 1995, Marinez et al 2000, Gray et al 2008. These studies have important application to understanding human eye disease.…”
Section: Cephalopodamentioning
confidence: 99%